2021
DOI: 10.1371/journal.pone.0261620
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and physicochemical properties as potential causes of stress in mangroves of the central Red Sea

Abstract: Mangrove ecosystems are some of the most productive and important sinks for sediment globally. Recently, there has been an increasing interest in possible causes of stress in mangroves, such as nutrient limitation, high salinity, solar radiation and temperature. We measured different factors casing stress and determined how they influenced oxidative stress and growth biomarkers in six study sites dominated by mangroves; Al Lith, South Jeddah, Dahban, Thuwal, Rabigh and Mastorah. Significant differences (P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
(81 reference statements)
1
3
0
Order By: Relevance
“…To use these microorganisms as plant growth promoters, we assessed their ability of AK164 to grow at moderately high temperatures (37 and 45 °C), and saline media (0–5 M NaCl) were assessed using Zobell marine agar (ZM) broth. Our data as well as previous data reported in the Red Sea coastal area showed that salinity reaches 35 PSU and high electrical conductivity of (39 uS/c) indicating higher dissolved sodium chloride in the soil (Alhassan and Aljahdali 2021 ).…”
Section: Methodssupporting
confidence: 91%
“…To use these microorganisms as plant growth promoters, we assessed their ability of AK164 to grow at moderately high temperatures (37 and 45 °C), and saline media (0–5 M NaCl) were assessed using Zobell marine agar (ZM) broth. Our data as well as previous data reported in the Red Sea coastal area showed that salinity reaches 35 PSU and high electrical conductivity of (39 uS/c) indicating higher dissolved sodium chloride in the soil (Alhassan and Aljahdali 2021 ).…”
Section: Methodssupporting
confidence: 91%
“…The high content of nitrogen (N) in leaves sampled from compartment 31 indicates the influence of anthropogenic activities such as agricultural activities in the catchment of the compartment [ 30 ]. Other causes could include increased N cycling associated directly with anthropogenic impacts [ 31 ]. Agricultural waste is a product of anthropogenic activities and could contribute to an increase in N values.…”
Section: Discussionmentioning
confidence: 99%
“…[ 32 ]. A possible influence of anthropogenic activities in mangrove ecosystems such as agricultural waste has been reported in the Matang mangrove ecosystem in Malaysia [ 1 ], New Zealand [ 33 ], and other impacted sites located in the central Red Sea [ 31 ]. In addition, other studies have also reported a high concentration of N in mangrove leaves compared to other mangrove tissues and sediment [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in salinity following rainfall reduction favored the formation of metal-chloride complexes, which are more stable in solution and thus more easily transported and also more bioavailable. Under arid conditions, stress conditions of mangroves, based on antioxidants content in leaves, showed salinity as the source of the biggest stress in Red Sea mangroves (Alhassan and Aljahdali, 2021). Under stressful conditions, the uptake of more bioavailable metals may eventually increase.…”
Section: Rainfall Reductionmentioning
confidence: 99%